Fault Tree Analysis of Nose Landing Gear Failure Function of Boeing 737-800 Next Generation Aircraft - Arif Pambekti; Yudha Misi Okia; Riski Kurniawan (Institut Teknologi Dirgantara Adisutjipto, 2025)
The retract actuator is one of the main parts of the landing gear, which functions to retract or extend. The retract actuator must be free in its operation and its movement must also be smooth. The aircraft experiences a functional failure if the retract actuator is in a slow to retract condition, where there is a slowdown during retract and extend. Careful initial handling is required and in accordance with aircraft maintenance handling procedures. Indications of initial failure can be obtained by connecting the same component maintenance log book on the same type of aircraft. This study uses the Fault Tree Analysis (FTA) method on the Boeing 737-800 Next Generation aircraft in the Merpati Maintenance Facility hangar. The source of data entered comes from the component maintenance log book on the aircraft with the same type. After the analysis was carried out, the minimum cut set results were obtained with calculations consisting of 18 basic events.